(untitled) (Eduscotech, 2022)
This community service project aims to analyze the roles and assessment criteria applied by adjudicators in speech contests held at Universitas Doktor Nugroho Magetan. As a platform for developing public speaking and rhetorical competence, speech contests play an essential role in enhancing students’ communication skills and academic self-development. Adjudicators hold a strategic function because their evaluations determine the fairness, quality, and credibility of the competition. This study employed a qualitative case study approach by collecting data through interviews with adjudicators, direct observations during the contest, and document analysis of assessment rubrics used in the event. The findings reveal that adjudicators apply four primary assessment dimensions: clarity and fluency of speech delivery, logical and coherent speech structure, the strength and originality of arguments, and the speaker’s ability to engage the audience. These dimensions strongly influence adjudicators’ scoring decisions and overall evaluation outcomes. Furthermore, the study highlights the need for standardized assessment guidelines to improve fairness, transparency, and consistency in future contests. The results are expected to contribute to enhancing the quality of speech contest adjudication and strengthening best practices for public speaking competitions in higher education settings.